Brand Experience, Brand Commitment, and Brand Loyalty of Xiaomi Smartphone Users in Magelang - Galuh Tiyasherlinda; Ivo Novitaningtyas (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
Increasingly technological developments and the increasing use of smartphones have led to competition between brands. Every smartphone company always innovates to meet the needs and desires of consumers, so that consumers will remain in one brand. The purpose of this study is to determine the effect of Brand Experience and Brand Commitment on Brand Loyalty of Xiaomi smartphone users, especially in the Magelang. This study uses a quantitative approach by distributing questionnaires to 100 respondents as a sample to obtain primary data. The sampling method used purposive sampling with the consideration that the respondents met the criteria, such as living in Magelang and currently using a Xiaomi smartphone. Multiple linear regression analysis with SPSS version 25 software was used as a data analysis technique. The results showed that Brand Experience had a positive effect but not significant on Brand Loyalty, while Brand Commitment had a positive and significant effect on Brand Loyalty. The results provide managerial implications for smartphone companies to provide brand experiences to users and increase user brand commitment to increase user loyalty to brands.